2023
DOI: 10.3390/pharmaceutics15030736
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib-Loaded Topical Nano-Emulgel for Rheumatoid Arthritis: Formulation Design and Optimization by QbD, In Vitro, Ex Vivo, and In Vivo Evaluation

Abstract: The current study aimed to develop a topical emulgel of dasatinib (DTB) for rheumatoid arthritis (RA) treatment to reduce systemic side effects. The quality by design (QbD) approach was employed to optimize DTB-loaded nano-emulgel using a central composite design (CCD). Emulgel was prepared using the hot emulsification method, and then the particle size (PS) was reduced using the homogenization technique. The PS and % entrapment efficiency (% EE) were found to be 172.53 ± 3.33 nm (0.160 ± 0.014 PDI) and 95.11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The stable formulations were further evaluated in freezethaw cycles. Three freeze-thaw cycles between − 21°C and + 25°C were performed at each temperature for not less than 48 hour and examined for changes in homogeneity and color [19,29].…”
Section: Thermodynamic Stability and Stress Testing (Centrifugation H...mentioning
confidence: 99%
“…The stable formulations were further evaluated in freezethaw cycles. Three freeze-thaw cycles between − 21°C and + 25°C were performed at each temperature for not less than 48 hour and examined for changes in homogeneity and color [19,29].…”
Section: Thermodynamic Stability and Stress Testing (Centrifugation H...mentioning
confidence: 99%
“…The drug content of all the samples ranged from 93.6% to 104.2% of labeled claims. According to the USP, a range of 90–110% for the labeled claim is acceptable [ 53 ]. Therefore, all the TIC formulations are accepted to be within the specified range of USP.…”
Section: Resultsmentioning
confidence: 99%
“…A 2022 study revealed the potential role of a microbial dye in combination with multiple low doses of gamma radiation exhibiting anti‐inflammatory effects and reducing disease severity in adjuvant induced arthritis rats (Abdel‐Rafei et al, 2022). Alternatively, nano‐carriers have also been explored for drug delivery against chronic inflammatory diseases (Oshi et al, 2022; Gorantla et al, 2020; Donthi et al, 2023). Recently, dendrimers have gained attention for their narrow polydispersity index (Dubey et al, 2021).…”
Section: Novel Potential Therapeutic Strategies Emerging Against Ramentioning
confidence: 99%
“…However, there have been advancements in the surgical sector such as prophylactic antibiotics and laminar airflow on the wound to prevent contamination, reducing joint infection incidences to a low 2%-2.4% (Goodman, 2015b). Alternatively, nano-carriers have also been explored for drug delivery against chronic inflammatory diseases (Oshi et al, 2022;Gorantla et al, 2020;Donthi et al, 2023). Recently, dendrimers have gained attention for their narrow polydispersity index (Dubey et al, 2021).…”
Section: Surgerymentioning
confidence: 99%